The constitution of Guyana - a study of its dysfunctional application - James, R. W. (2006)
Looks at the formative years, the power structure and the control of the executive. Focuses on the supremacy of the constitution. Highlights social problems, outside intervention and long and short term changes. Provides conclusions.